Association between feeding methods and sleep status at one month postpartum: a linkage study among six cities of 757 women at 1 month postpartum - Weiming WANG; Junai GAN; Xianfeng ZHAO; Na LI; Yaxin ZHAO; Zhixu WANG; Guo ZENG; Nianhong YANG (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo explore the association between feeding methods at 1 month postpartum and maternal sleep status. MethodsFrom November 2021 to September 2022, a total of 757 postpartum women at 1 month postpartum in Nanjing, Chengdu, Xi'an, Wuhan, Guangzhou, and Qingdao were surveyed by face-to-face to collect information on infant feeding methods and sleep status of 1 monthpostpartum women. The study subjects were divided into four groups according to the feeding methods: (1) exclusive breastfeeding, (2) exclusive breastfeeding/bottle-feeding, (3) mixed feeding - breastfeeding, and (4) mixed feeding - breastfeeding/bottle-feeding. A generalized linear model was used to analyze the association between feeding method and sleep duration of postpartum women. A multinomial logistic regression model was used to analyze the association between feeding method and the risk of insufficient or excessive total sleep duration and subjective sleep quality in postpartum women. ResultsThe number of women in the exclusive breastfeeding, exclusive breastfeeding/bottle-feeding, mixed feeding - breastfeeding, and mixed feeding - breastfeeding/bottle-feeding groups was 263, 173, 152, and 169, respectively, and the total sleep duration was (8.4 ± 1.7), (7.8 ± 1.5), (8.3 ± 1.8), and (8.1 ± 1.7) hours, respectively. After adjusting for potential confounding factors, compared with mothers who exclusively breastfed, total sleep duration and night sleep duration were reduced by 0.7 and 0.5 hours, respectively, in mothers who exclusively breastfed/bottle-fed and mothers who mixed fed - breastfed/bottle-fed (P < 0.05). The risk of insufficient total sleep duration (< 7 h) was significantly increased in the exclusive breastfeeding/bottle-feeding group, with an adjusted OR (95%CI) of 2.07 (1.16 - 3.72). The risk of poor or very poor subjective sleep quality was significantly increased in the exclusive breastfeeding/bottle-feeding group, mixed feeding - breastfeeding group, and mixed feedin - breastfeeding/bottle-feeding group, with adjusted OR (95%CI) of 3.11 (1.52 - 6.35), 2.31 (1.02 - 5.22), and 3.00 (1.32 - 6.80), respectively. ConclusionPostpartum women who exclusively breastfed had longer sleep duration and the best subjective sleep quality.